Nurses best practices for the management of thrombotic thrombocytopenic purpura. Issue 3 (June 2018) - Harmon, Pamela; Cojocari, Eduard; Mader, Catherine Lynn; Galloway, Charlene; Buchholz, Megan; Lewis, Brenda; Sinclair, Susan
Abstract: A group of Canadian apheresis nurses developed best practice for in the management of thrombotic thrombocytopenic purpura (TTP). The recommendations address issues related to infusion protocols, preventing and managing adverse events, comprehensive patient assessments, treatment procedures, as well as pre- and post- treatment care. The Canadian group encourages institutes to include nurses on committees that examine recommendations for TTP management.